2011
DOI: 10.5430/ijba.v2n3p83
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Relationship Marketing Tactics on Customer Loyalty: The Mediation Role of Relationship Quality

Abstract: Concerning potential importance of retaining customers and establishing right relationship with them to create loyalty, previous studies have presented diverse results which can be related to lack of an appropriate relationship quality. Therefore, this study was conduced in Karafarin Insurance Representatives in Mashhad, Iran for identifying Relationship Marketing (RM) tactics impacts on loyalty due to Relationship Quality (RQ). The RM tactics under investigation were tangible reward, interpersonal communicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
1
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 27 publications
(23 reference statements)
1
13
1
3
Order By: Relevance
“…This highlights that the quality of relationship influences customer behavioral responses. This confirmed that relationship quality is very important to create or building customer loyalty and then create competitive advantage (Doaei et al, 2011).…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…This highlights that the quality of relationship influences customer behavioral responses. This confirmed that relationship quality is very important to create or building customer loyalty and then create competitive advantage (Doaei et al, 2011).…”
Section: Discussionmentioning
confidence: 59%
“…It also refers to the consumer's overall assessment of the relationship strength and the extent to which it fulfills the consumer's expectations based on their experience with the business firm (Crosby, Evans, Cowles, 1990;Smith, 1998, p. 78). Relationship quality literature confirmed that it is a multi-dimensional construct, which consists of three interrelated constructs namely customer satisfaction, trust, and commitment that may help to reduce consumer's uncertainty feelings concerning its relation with the service provider (Morgan and Hunt, 1994;Dorsch, Swanson, Kelley, 1998;Woo and Ennew, 2004;Vesel and Zabkar, 2010;Doaei, Rezaei and Khajei, 2011;Kim Jung-Eun and Lee, 2012).…”
Section: Relationship Quality (Rq)mentioning
confidence: 99%
“…CRMTs that were insignificant for both banks include tangible reward, supported by Tseng (2007) and Horri, Shirsavar, and Mohaved (2013). However, this finding was opposed with the study by Doaei et al, (2011). Next is interpersonal communication and this is also supported by Tseng (2007) and was opposed by Doaei et al, (2011) and Lo, Lycnh and Staelin (2007).…”
Section: Resultsmentioning
confidence: 85%
“…Meanwhile, another three CRMTs which are direct mail, interpersonal communication and tangible reward are not significant for banking industry. Doaei, Rezaei and Khajei (2011) had used the same model as Tseng (2007) however; researchers tested four tactics out of five that exclude the membership. Researchers covered that, all the CRMTs were significant in generating of customer loyalty except preferential treatment.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Menurut Mittal, et al (Doaei, 2011) bahwa salah satu faktor yang mempengaruhi behavioral loyalty adalah tingkat kepuasan pelanggan. Hasil temuan yang dilakukan oleh beberapa penelitian terdahulu, seperti ), Ardyansyah (2007, Yen and Gwinner (2003); Hennig- Thurau et al (2002); Yen, Liu, and Tuan (2009); Prayustika dan Adriani(2010); Semadi et al (2010)…”
Section: Hasil Dan Pembahasan Tabel 1 Rangkuman Persamaan Jalurunclassified